Perjanjian Waralaba : Penerapan dalam Konteks Modern - Novie Afif Mauludin (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
This research aims to determine the application of franchise agreements in a modern context. The research method used is normative juridical which is descriptive analytical in nature, using primary, secondary and tertiary data. A normative juridical approach with a systematic analysis of the legal provisions governing the phenomenon under study using various types of data such as relevant laws and legal literature. The conclusion obtained is that the application of the Franchise Agreement in the Modern context is made online and is legally valid and has the power of proof as per Article 5 of Law Number 11 of 2008 concerning Electronic Information and Transactions in conjunction with Article 46 of the Government Regulation of the Republic of Indonesia Number 71 of 2019 concerning Implementation Electronic Systems and Transactions. Then, if there is a settlement between the parties by means of non-litigation or outside court based on the provisions of Law of the Republic of Indonesia Number 30 of 1999 concerning Arbitration and Dispute Resolution or by litigation through a general court, namely a district court whose jurisdiction or area of ??authority has been determined by the parties. party. Legal provisions that can be used when disputing through court refer to Article 1243 of the Civil Code relating to compensation for losses due to broken promises or default. And termination of the agreement by one of the parties can be subject to sanctions in accordance with Article 16 paragraph (2) Government Regulation no. 42 of 2007 concerning Franchising.